Urgensi Peran Konsultan Akademik dalam Proses Pencapaian Merdeka Belajar Kampus Merdeka di Perguruan Tinggi Swasta - Chaerunisyah, Ana (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2023)
The role of academic consultants in higher education is pivotal, transcending traditional academic guidance. This paper underscores their significance in aiding students to navigate academic challenges while preparing for an evolving job market. Dr. Sophia Roberts emphasizes their dual role in imparting contemporary information on educational options, curricula, and career prospects, while also facilitating personalized guidance tailored to individual student needs. Dr. David Yang echoes this, highlighting the consultants' responsibility in cultivating skills relevant to the dynamic workforce, such as problem-solving, communication, and adaptability. These experts accentuate the consultants' pivotal role in bridging the gap between academic knowledge and practical job requirements. Ultimately, academic consultants serve as holistic supporters, not just focusing on academic success but also ensuring students are practically equipped for the diverse demands of the professional world.